Application of Role Playing Method to Increase Student Activity in Learning Indonesian Class II SDN 2 Gowak - Husna, Laela Nadhia (Prosiding University Research Colloquium, 2021)
This study aims to increase student activity in Indonesian language subjects through the application of the Role Playing method. The research method used is Classroom Action Research (CAR). The subjects of the study were the second grade students of SDN 2 Gowak, totaling 10 students consisting of 4 male students and 6 female students. The results showed that the activeness of students increased from the first cycle and second cycle. In the initial data, there are no students who have a very active category, students with an active category are 10%, a moderately active category is 30% and a less active category is 60%. After taking action in cycle I with the Role Playing method, the activity increased. Students in the very active category are 10%, the active category is 20%, the moderately active category is 40% and the less active category is 30%. In the second cycle there was an increase in the very active category 40%, the active category 40%, the moderately active category 20% and the less active category 0%. So it can be concluded that the Role Playing method is able to increase the activity of second grade students at SDN 2 Gowak.